The application of methylene blue coloration technique in axillary lymph node dissection of breast cancer - Zou, Jieya; Wang, Xiaoqi; Yang, Zhuangqing; Yang, Xiaojuan; Wang, Chang’an; Sun, Lifei; Wang, Wenhuan; Wang, Yue; Nie, Jianyun (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: To analyze the associated factors that affect the coloration of methylene blue (MB) in axillary lymph node dissection (ALND) of patients with breast cancer and to explore the tracer effect of MB in high axillary lymph node metastasis, to guide surgical treatment. Methods: We recruited 170 patients who underwent ALND, all of them were injected MB before operation. We analyzed the relationships between the clinical factors of age, body mass index (BMI), molecular typing, TNM staging, neoadjuvant chemotherapy, injection time and position and the MB coloration by univariate and multivariate analyses. A total of 84 cases were selected for observation of the application value of MB during intervention involving the lymph nodes upper axillary vein. Results: Of 170 cases, 138 cases (81.17%) were colored. Univariate analysis showed that significant differences were observed between differing BMI’s (χ2=24.074, P